X-ray diffraction data for "Breaking the Symmetry of a Meso Compound by Isotopic Substitution: Synthesis and Stereochemical Assignment of Monodeuterated cis-Perhydroazulene" - Saito, Fumito; Becker, Jonathan; Schreiner, Peter R.; Justus Liebig University Giessen (My University, 2020)
Raw X-ray diffraction images for the publication F. Saito, D. Gerbig, J. Becker, P. R. Schreiner, Org. Lett. 2021, 23, 1, 113–117 ( https://pubs.acs.org/doi/full/10.1021/acs.orglett.0c03795 ) File format is the Bruker sfrm frame format. The data can be processed with the SAINT program by BRUKER AXS or using alternative and/or open source tools as XDS ( http://xds.mpimf-heidelberg.mpg.de/ ) together with sfrmtools ( https://homepage.univie.ac.at/tim.gruene/research/programs/conv/sfrmtools/ ) or FabIO ( Knudsen, E. B., Sorensen, H. O., Wright, J. P., Goret, G. & Kieffer, J. (2013). J. Appl. Cryst. 46, 537-539. ). FabIO provides the following information about the file format: "The bruker format uses 80 char lines in key : value format. In the first 512*5 bytes of the header there should be a HDRBLKS key, whose value denotes how many 512 byte blocks are in the total header. The header is always n*5*512 bytes, otherwise it wont contain whole key: value pairs. Data is stored in three blocks: 1. data (uint8) 2. overflow (uint32) 3. underflow (int32). The blocks are zero padded to a multiple of 16 bits.
Keywords: X-ray diffraction; Single crystal diffraction; Organic chemistry; ddc:540